Aktualisasi Metode Bernyanyi dalam Pembelajaran Fiqih di MI Al Asy’ari Keras Diwek Jombang - Adeliya Siti Napi'ah (Universitas Islam Tribakti Lirboyo Kediri, 2023)
This study aims to describe the implementation of the singing method in learning fiqh. The approach used in this research is qualitative and the type of research is a case study. So the data in this study were obtained by means of interviews, observation and documentation. The data obtained were analyzed using descriptive techniques with three streams of activities, namely: Data condensation, Data Presentation, and Conclusion Drawing and data validity testing. The results of this study show that the implementation of the method of singing fiqh learning materials with a social constructivism approach is carried out by referring to the three domains of education including cognitive, affective and psychomotor. The learning delivery strategy emphasizes what activities students do, the learning structure used and the media used in delivering learning materials.